NILAI RUJUKAN FREE LIGHT CHAIN SERUM DENGAN IMUNOTURBIDIMETRI - Lidya Utami; Riadi Wirawan; Alida R Harahap; Abdul Muthalib; Harny Edward (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2012)
The light chains of immunoglobulin are produced in larger quantity rather than heavy chains, therefore small amount of free lightchains (FLC) can be found in the blood of healthy individuals. Free light chain production is increased in the clone’s proliferation ofmalignant B cells, i.e. in myeloma. Therefore the FLC level measurement can be used for diagnosis aid of myeloma and related B cellsdisorders. The aim of this study is to establish reference range of serum FLC κ, FLC λ, and κ/λ ratio in population ≥40 year’s old usingimmunoturbidimetry assay. Serum FLC κ, FLC λ and κ/λ ratio were measured in 240 healthy male and female attending medical checkup in MMC hospital. Healthy subjects were determined by anamnesis and physical examination, with routine haematology, ESR, andserum creatinine level within normal ranges. The serum FLC assays were performed in the Clinical Pathology Laboratory, RSCM, usingHitachi 912 with immunoturbidimetry method. The results were analyzed by SPSS 11.5 program. Serum FLC normal reference valuein 40-84 years old healthy subjects are: FLC κ 11.7–30.6 mg/L, FLC λ 9.7–25.0 mg/L, and κ/λ ratio 0.79–1.75. This research is thefirst study for finding serum FLC values in the Indonesian population. The normal reference value found is similar with another studyusing the same platform analyzer.